Optimalisasi Sistem Pelayanan Administrasi di Badan Kepegawaian Daerah Provinsi Kalimantan Tengah - Siti Maisarah; Nurul Hikmah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
This research examines the optimization of the administrative service system at the Regional Personnel Agency of Central Kalimantan Province using a descriptive qualitative approach. The focus of the research includes the implementation of the service system, identification of obstacles, and development of a resolution strategy. The results revealed that the administrative service system has been implemented through six main aspects that are integrated with each other, including guest services, management of incoming letters and dispositions, numbering of outgoing letters, reporting on letter administration, file distribution, and distribution of Decision Letters (SK). The main obstacle identified is the management of non-physical incoming mail that has not been well organized, but has been overcome through a systematic search strategy and intensive internal communication. Efforts to improve service quality are implemented comprehensively through the development of employee competencies, strengthening work integrity, periodic evaluations, and building a culture of excellent service, all of which contribute to improving the effectiveness of the overall administrative service system.